Toxicity of Carnoy's solution toward human keratinocytes: an in vitro study - Pinto Júnior,Aécio Abner Campos (2021)
Abstract: The present study aimed to characterize the chemical elements and cytotoxicity of Carnoy's solution (CS) by comparing two different trademarked products (one Brazilian [NCS] and another imported [ICS]) using inductively coupled plasma mass spectrometry (ICP-MS) and human keratinocyte (HaCaT) cultures. For performing ICP-MS, the solutions were diluted according to calibration curves, and the chemical elements were analyzed with a spectrometer. HaCaT cells were exposed to CS concentrations ranging from 0.10% to 20% for 3 or 5 min. Cell viability was evaluated immediately (T0), 24 h (T1), and 7 days (T2) after exposure to CS using 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide (MTT) reduction assay. Data were analyzed using a t-test for ICP-MS and analysis of variance followed by Tukey's post-hoc test for MTT assay, both considering statistical significance at p<0.05. ICP-MS results revealed that ICS presented significantly lower concentrations of 12 chemical elements than NCS. The results of MTT assay revealed that at T0, ICS was more cytotoxic than NCS regardless of the time of exposure (p < 0.05). At T1, the only difference between the groups was at a concentration of 0.10% after 5 min of exposure. At T2, at a concentration of 0.5%, ICS resulted in a significant reduction in cell viability compared to NCS (p < 0.05). Thus, the results showed that ICS was more cytotoxic than NCS. Collectively, our findings suggest that the individual compositions of different CS formulations should be investigated.